PLATELET PROFILE OF BALINESE CATTLE IN DENPASAR, BALI - Siswanto; I Nyoman Sulabda (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Bali cattle (Bos javanicus) are a genetic resource native to Indonesia and play a crucial role in meeting national meat demand. Understanding hematological parameters, including platelet profiles, is essential for assessing the physiological condition and health of livestock. This study aimed to determine the platelet profile in healthy Bali cattle as a basis for establishing specific hematological reference values ​​for this local cattle breed. Blood samples were taken from 20 healthy Bali cattle using EDTA tubes, then hematological analysis was performed using a Licare CC 3200Vet Veterinary Hematology Analyzer. The results showed that the mean platelet count (PQ), platelet distribution width (PDW), platelet crit (PCT), platelet large cell count (P-LCC), and platelet large cell ratio (P-LCR) were equal or similar to the reference values. Meanwhile, the mean platelet volume (MPV) was significantly higher than the reference value. These data are expected to serve as a baseline for further research and as supporting information for the development and preservation of Bali cattle as Indonesia's superior germplasm.